Performa dan Profil Beberapa Komponen Darah Sapi Peranakan Ongole yang Diberi Pakan Mengandung Lerak (Sapindus rarak De Candole) - D A Astuti; E Wina; B Haryanto; S Suharti (Faculty of Animal Science, Bogor Agricultural University, 2009)
The problem with low meat production is caused by several factors, ie: management, feed and animal health. The development of integration system such as cattle-rice, cattle-corn and cattle-palm oil aims to utilize feed from local resources. However, sometimes local feedstuff causes a problem of imbalance nutrient. There are several strategies to overcome this problem and one of them is the use of feed additives from natural substance or plant resources such as lerak (Sapindus rarak De Candole). This research was aimed to utilize lerak fruit to improve performance and evaluate some blood profiles of Ongole crossbred cattle. The in vivo work was done using 12 Ongole crossbred cattle receiving 3 different feeds as treatment, i.e. 1) feed without lerak (high roughage diet) as control, 2) feed contained 2,5% lerak, and 3) feed contained 5% lerak. Growth, daily gain, blood profiles (leucocytes, cholesterol, trigliceride and globulins) were observed. The results showed no significant differences for nutrient intake, meaning that the ration has good palatability. Average daily gain of cattle fed with 2,5% lerak was 20% higher than those with control diet. White blood cells tended to decrease caused by lerak treatments, but the globulin profiles (alpha, beta and gamma) were not significantly affected in all treatments. Blood cholesterol concentration decreased following the increase of lerak percentage. It is not recommended to use lerak in the cattle ration for more than two months because of the decreasing of leucocytes. Key words: Sapindus rarak, in vivo, leucocytes, globulins, palatability